2002
DOI: 10.1139/f02-021
|View full text |Cite
|
Sign up to set email alerts
|

Regional patterns in periphyton accrual and diatom assemblage structure in a heterogeneous nutrient landscape

Abstract: The effect of nutrient regime on periphyton community development in large rivers was examined (sites ranged from oligotrophic to eutrophic). Patterns in diatom community structure were examined at a large spatial scale (ultimate), whereas at the microhabitat scale (proximate), artificial nutrient-diffusing substrata were used to examine periphyton response to amendment with nitrogen, phosphorus, and N + P. Ratios of ambient dissolved inorganic nitrogen to total phosphorus were used to make predictions of nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Its predictions should be tested and potentially extended to other communities, whose functioning depends on species 3D coexistence. For example, in lacustrine phytobenthos, eutrophication increases species richness (36) and alters the spatial organization of the benthic mat in a manner identical to the patterns described here for streams (37). Similarly to stream diatoms, the coexistence of encrusting and turf-forming macroalgae as a two-story community in marine subtidal systems is driven by species' abilities to tolerate vs. overgrow (13).…”
Section: Resultsmentioning
confidence: 58%
“…Its predictions should be tested and potentially extended to other communities, whose functioning depends on species 3D coexistence. For example, in lacustrine phytobenthos, eutrophication increases species richness (36) and alters the spatial organization of the benthic mat in a manner identical to the patterns described here for streams (37). Similarly to stream diatoms, the coexistence of encrusting and turf-forming macroalgae as a two-story community in marine subtidal systems is driven by species' abilities to tolerate vs. overgrow (13).…”
Section: Resultsmentioning
confidence: 58%
“…Light, climate, geology, land use, substrate size, and vegetation all have been identified as factors that can control algal populations in addition to nutrient conditions and related water chemistry parameters. In some cases, algal biomass and community structure are related more to factors measured at larger scales such as land use (Leland and Porter 2000;Snyder et al 2002;Taylor et al 2004) or patterns in hydrology (Biggs 1996;Biggs and Smith 2002) than to nutrients measured at local and ephemeral scales. Although broad-scale factors have been related to algal biomass and community structure, the hierarchical arrangement of these factors has received less attention (Stevenson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Woods (1982) found that signifi cant amounts of nutrients and organic matter were being retained by the reservoir formed by completion of the dam. The reservoir was subsequently linked to signifi cant phosphorus limitation of periphyton in river reaches below the dam and the potential for autotrophic food limitation (Snyder et al, 2002). Beginning in 1991, water release through the dam simulated the historic fl ow regime, although discharge typically only reaches 60 % of the historic average spring value of 1840 m 3 s -1 and velocities are less than 1 m s -1 (Coutant, 2004).…”
Section: Introductionmentioning
confidence: 99%